Sistem Pendukung Keputusan Kelurahan Terbaik Di Kecamatan Padang Hulu Kota Tebing Tinggi Menerapkan Metode Weighted Aggregated Sum Product Assesment (WASPAS): Array - Iqbal, Muhammad; Aripin, Soeb; Azhari, Isa (JiTEKH, 2022)
This Decision Support System is to facilitate the selection stage of the best Kelurahan which is held by the District of Padang Hulu, Kota Tebing Tinggi. Kelurahan is the division of administrative areas in Indonesia under sub-districts. Kelurahan is the work area of ​​the lurah as a Regency or City regional apparatus. One of the efforts carried out by the best kelurahan is to encourage development carried out by the kelurahan on the basis of their own determination and strength and to determine the kelurahan that excels in the implementation of community empowerment. Decision Support System (DSS) is a system that is able to provide problem solving skills and communication skills for problems with structured and unstructured conditions. DSS aims to provide information, guide, provide predictions and direct information users so that they can make better decisions. This system is a Decision Support System (DSS) which was built using the Weighted Aggregated Sum Product Assessment (WASPAS) method. Data processing will be carried out by a selection team from the Padang Hulu sub-district office by entering the value of each sub-district in Padang Hulu District, Tebing Tinggi City. Then the system will perform calculations according to the provisions of the Weighted Aggregated Sum Product Assessment (WASPAS) method which ultimately results in a ranking that can help the selection team of the Padang Hulu District Office of Tebing Tinggi City in comparing the rankings obtained. The system built using the WASPAS method has been able to determine which village is the best in Padang Hulu District, Tebing Tinggi City.